Effect of season and age on biochemical, antioxidant and oxidative profiles in mithun bull - PERUMAL, P; KHATE, K; VUPRU, K (The Indian Journal of Animal Sciences, 2022)
Mithun (Bos frontalis) is a domesticated free-range bovine species primarily used as a meat animal and is apride of North Eastern Hilly regions of India. The present study was conducted to measure the effect of season onbiochemical, and antioxidant and oxidative stress profiles for different age groups at different seasons in mithunbulls. A total of 30 mithun males were selected from the mithun breeding farm, ICAR-NRC on Mithun, Medziphema,Nagaland and were equally divided into five classes based on their age. Each group consisted of six animals andthe groups were Gr A, Gr B, Gr C, Gr D and Gr E. Seasons were categorised into winter, spring, summer andautumn based on the meteorological parameters such as temperature humidity index (THI) and sunshine hours.Biochemical indices such as total protein, albumin, globulin, glucose and total cholesterol; antioxidant profilessuch as total antioxidant capacity (TAC), catalase (CAT), glutathione (GSH), glutathione reductase (GSHR) andsuperoxide dismutase (SOD); and oxidative profile such as malondialdehyde (MDA) were estimated. Statisticalresults revealed that these experimental profiles differed significantly between the different age groups for thedifferent seasons and between the seasons for different age groups. Blood biochemical indices increased significantlyas age advanced and higher concentration in spring and winter than in summer season. TAC, CAT, GSH, GSHRand SOD were significantly greater and MDA was significantly lower in spring and winter than in summer season.The antioxidants increased significantly from Gr A to Gr B and then reduced gradually to Gr E, whereas concentrationof MDA significantly increased as the age advanced. It can be concluded that spring and winter season hassignificantly greater beneficial effects than summer season on production and reproduction programme in semiintensivemanagement of mithun in tropical humid hilly ecosystem of Nagaland.